The interaction of testosterone and cortisol is associated with attained status in male executives. [article]. - Sherman, Gary D.
Are hormone levels associated with the attainment of social status? Although endogenous testosterone predicts status-seeking social behaviors, research suggests that the stress hormone cortisol may inhibit testosterone's effects. Thus, individuals with both high testosterone and low cortisol may be especially likely to occupy high-status positions in social hierarchies while individuals with high testosterone and high cortisol may not. We tested this hypothesis by recruiting a sample of real executives and examining testosterone, cortisol, and a concrete indicator of attained status: the number of subordinates over which the executive has authority. Despite the myriad nonhormonal factors that determine organizational promotion, the executives' endogenous testosterone and cortisol interacted to significantly predict hierarchical position: Testosterone positively predicted executives' number of subordinates, but only among low-cortisol executives. The results imply that reducing cortisol levels via stress reduction may be a critical goal not only because doing so will improve health but also because doing so may enhance leadership potential. -- (from the authors)
Keywords: Lerner, Jennifer S; Sociometer theory versus self-broadcasting theory; Power; Social status; Hormones; Neuroendocrine; Stress